Dampak pelatihan, pengalaman, dan lingkungan kerja fisik terhadap produktivitas kerja karyawan PT.X bagian produksi Plywood - Pawitri, Afina Rosse; Febriana, Artha (Journal of Management and Digital Business, 2025)
Human resources (HR) plays a crucial role in driving the progress and success of an organization. The abilities, knowledge, and skills of employees have a direct impact on productivity. To face increasingly fierce business competition, companies must improve employee productivity to compete quickly and efficiently. This study aims to analyze the impact of training, experience, and physical work environment on employee productivity in PT.X. Data was gathered from 102 respondents in the plywood production department using a purposive sampling method with a descriptive quantitative approach applied in the study. The impact of training, experience, and the physical work environment on productivity was assessed using multiple linear regression methods. The results of this study show that job training has a significant effect on employee productivity, while experience and physical work environment do not show a significant effect. This indicates that improving skills through training is more effective in driving productivity than work experience and physical working environment conditions. Therefore, companies are advised to prioritize training programs on an ongoing basis to improve employee capabilities and work efficiency.